Partial melting of zoisite eclogite from the Sanddal area, North-East Greenland Caledonides - Cao, Wentao; Gilotti, Jane A.; Massonne, Hans-Joachim (European Journal of Mineralogy, 2020)
Metamorphic textures and a pressure–temperature (P–T) path of zoisite eclogite are presented to better understand the metamorphic evolution of the North-East Greenland eclogite province and this particular type of eclogite. The eclogite contained the mineral assemblage garnet, omphacite, kyanite, phengite, quartz and rutile at peak pressure. Partial melting occurred via breakdown of hydrous phases, paragonite, phengite and zoisite, based on (1) polymineralic inclusions of albite and K-feldspar with cusps into host garnet, (2) small euhedral garnet with straight boundaries against plagioclase, (3) cusps of plagioclase into surrounding phases (such as garnet), and (4) graphic intergrowth of plagioclase and amphibole next to anhedral zoisite grains. Isochemical phase equilibrium modeling of a melt-reintegrated composition, along with XNa-in-omphacite and Si-in-phengite isopleths, yields a peak pressure of 2.4±0.1 GPa at 830±30 ∘C. A peak temperature of 900±50 ∘C at 1.9±0.2 GPa is determined using the rim composition of small euhedral garnet, as predicted by modeling a crystallized melt pocket. Zoisite growth at the expense of kyanite suggests that the P–T path crossed the fields of zoisite growth at ∼1.9 GPa, 800–900 ∘C on the modeled phase diagram of the bulk rock. A point on the exhumation path at ∼1.3 GPa and 750 ∘C is derived from hornblende-plagioclase thermometry and Al-in-hornblende barometry. The study demonstrates that paragonite, phengite and zoisite could contribute to partial melting of eclogite at near-peak P and during exhumation.